Simultaneous determination of Cu(II), Zn(II), and Pb(II) from aqueous solutions using a polymer inclusion membrane (PIM) based-sensor with 1-(2-pyridylazo)-2-naphthol (PAN) as chromophore and chemometric methods - Mancilla-Rico, Alejandro J.; Rodríguez de San Miguel, Eduardo (Frontiers in Analytical Science, 2022)
Polymer inclusion membranes (PIMs) were developed to be used as colorimetric sensors for the simultaneous determination and quantification of Cu(II), Zn(II), Pb(II) from aqueous solutions using chemometric methods. Different physical and chemical factors that influence the detection process of the analytes were studied, i.e., the concentration of the metal cation, the amount of membrane, and the pH of the solution. The reversibility and durability of the signal were evaluated as well. The simultaneous calibration for three metal cations by the partial least squares (PLS) algorithm was performed with an experimental central composite design matrix with five levels and three experimental factors. The construction of the calibration model was carried out from the information obtained from the UV – VIS spectrum of the PIMs exposed to the aqueous solutions. The predictive power of the calibration model for each of the metal cations was evaluated contemplating two different matrices of synthetic water. Principal component analysis (PCA) was in addition employed to visualize patterns in the synthesized membranes.